Net traction of a driven wheel as affected by slippage, velocity and wheel load - Hamid Taghavifar; Aref Mardani (Journal of the Saudi Society of Agricultural Sciences, 2015)
The objective was to assess the effect of velocity at three levels (i.e. 0.8, 1 and 1.2 m/s), slippage at three levels (i.e. 10, 12 and 15%) and three levels of wheel load (i.e. 2, 3 and 4 kN) on net traction utilizing a single-wheel tester in the soil bin facility of the Department of Agricultural Machinery of Urmia University. Analysis of variance (ANOVA) was developed to verify the effectiveness of the aforementioned parameters on the objective of the study at 1% significance level. It was found that the increment of wheel load and slippage results in the increment of net traction. However, it was deduced that velocity has no significant effect on net traction.